First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Conservation resource allocation, small population resiliency, and the fallacy of conservation triage - David A. Wiedenfeld; Allison C. Alberts; Ariadne Angulo; Elizabeth L. Bennett; Onnie Byers; Topiltzin Contreras‐MacBeath; Gláucia Drummond; Gustavo A. B. da Fonseca; Claude Gascon; Ian Harrison; Nicolas Heard; Axel Hochkirch; et al. (Conservation Biology, 2021)
Some conservation prioritization methods are based on the assumption that conservation needs overwhelm current resources and not all species can be conserved; therefore, a conservation triage scheme (i.e., when the system is overwhelmed, species should be divided into three groups based on likelihood of survival, and efforts should be focused on those species in the group with the best survival prospects and reduced or denied to those in the group with no survival prospects and to those in the group not needing special efforts for their conservation) is necessary to guide resource allocation. We argue that this decision‐making strategy is not appropriate because resources are not as limited as often assumed, and it is not evident that there are species that cannot be conserved. Small population size alone, for example, does not doom a species to extinction; plants, reptiles, birds, and mammals offer examples. Although resources dedicated to conserving all threatened species are insufficient at present, the world's economic resources are vast, and greater resources could be dedicated toward species conservation. The political framework for species conservation has improved, with initiatives such as the UN Sustainable Development Goals and other international agreements, funding mechanisms such as The Global Environment Facility, and the rise of many nongovernmental organizations with nimble, rapid‐response small grants programs. For a prioritization system to allow no extinctions, zero extinctions must be an explicit goal of the system. Extinction is not inevitable, and should not be acceptable. A goal of no human‐induced extinctions is imperative given the irreversibility of species loss.

Nature-Based Social Prescribing in Urban Settings to Improve Social Connectedness and Mental Well-being: a Review - M. A. Leavell; J. A. Leiferman; M. Gascon; F. Braddick; J. C. Gonzalez; J. S. Litt (Current Environmental Health Reports, 2019)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Ecosystem Decay of Amazonian Forest Fragments: a 22‐Year Investigation - William F. Laurance; Thomas E. Lovejoy; Heraldo L. Vasconcelos; Emilio M. Bruna; Raphael K. Didham; Philip C. Stouffer; Claude Gascon; Richard O. Bierregaard; Susan G. Laurance; Erica Sampaio (Conservation Biology, 2002)
We synthesized key findings from the Biological Dynamics of Forest Fragments Project, the world's largest and longest‐running experimental study of habitat fragmentation. Although initially designed to assess the influence of fragment area on Amazonian biotas, the project has yielded insights that go far beyond the original scope of the study. Results suggest that edge effects play a key role in fragment dynamics, that the matrix has a major influence on fragment connectivity and functioning, and that many Amazonian species avoid even small (